(untitled) - Ibsen, Olga A. C.; Olga A.C. Ibsen; Joan Andersen Phelan (St. Louis, Mo.)
Oral Pathology for the Dental Hygienist is your source for the most trusted content in oral pathology. With more than 50 years of combined real-world experience, Olga Ibsen and Joan Phelan have created a text that offers the ideal combination of clinical photographs, radiographs and discussion to help you identify, understand, evaluate, and document the appearance of normal and disease states. This user-friendly, atlas-style text features the learning tools and updated content you need to prepare for success on your exams and throughout your professional career
Includes bibliographical references and index
Keywords: Dental hygienists; Mouth; Mouth Diseases; Tooth Diseases